(untitled) - Barh, Debmalya (Boca Raton, FL, 2014)
Merging topical data from recently published review and research articles, as well as the knowledge and insight of industry experts, Omics Applications in Crop Science delves into plant science, and various technologies that use omics in agriculture.
Keywords: Khoa học cây trồng,Crops,Crop science; Postharvest technology